ANALISIS STRATEGI DALAM MENENTUKAN PENDAPATAN USAHA TAMBAK UDANG PADA KELOMPOK TANI DESA TAMBAKSUMUR KECAMATAN TIRTAJAYA KARAWANG - Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (Indonesian Journal of Strategic Management, 2025)
The purpose of this study is to know, explain, and analyze the income conditions and what strategies are used to increase pond shrimp income in the Shrimp Pond Farmer Group of Tambak Sumur Village, Tirtajaya District, Karawang. This study uses a Qualitative Descriptive method using SWOT analysis techniques, the data collection used in this study uses primary data, which is obtained through direct interviews. The high demand for shrimp encourages the development of shrimp farming businesses in several regions in Indonesia. Tirtajaya District is one of the sub-districts in Karawang district that has agriculture, most of the Tirtajaya people make a living as farmers and have a pond land of 4,200 hectares. The number of pond farmers who were sampled in this study was 8 farmers with the results of the study showing that the strength (strenght) is owned by experienced people and the average length of business starts from 7-15 years of doing business. The weakness of this business depends on water, and the season when the conditions are dry, the temperature is very hot and drought occurs, there will be a possibility of crop failure. Then shrimp that have been harvested also have a risk of rotting quickly. Opportunities for shrimp commodities that dominate total exports in Indonesia's fisheries sector and receive full support from the Ministry of Marine Affairs and Fisheries, as well as the Marine and Fisheries Service in Karawang Regency with the program being run. And the threats of shrimp crops are not always loud. The strategy that must be carried out is to intensely communicate with the government so that monitoring is carried out in the maintenance process to find out the possibility of failure that occurs, and on the other hand it expands the marketing network